Adat sebagai Hukum: Tinjauan atas Kaidah al-‘Adah Muhakkamah dan Penerapannya dalam Realitas Sosial - Anggi Egi Anggraini (P2WP MUI Sumatera Utara, 2024)
The legal maxim al-‘adah muhakkamah states that customs widely practiced within a society can serve as a legal basis, provided they do not contradict Islamic law. Custom plays a significant role in both social and religious life, demonstrating the flexibility and adaptability of Sharia to social dynamics. However, not all customs are acceptable, which necessitates clear requirements and limitations. This study aims to examine the maxim al-‘adah muhakkamah, identify its subsidiary principles, and analyze its practical application in society. The research employs a normative legal method with historical and conceptual approaches, focusing on classical and contemporary Islamic jurisprudence sources. The findings reveal that this maxim is not merely theoretical but holds practical legal authority. Customs that are continuously practiced and do not conflict with Sharia serve as a legitimate source of law in resolving various issues in muamalah. This demonstrates that Islamic law remains dynamic and applicable in accordance with the evolving realities of Muslim societies.